Developing a Model of Tendency toward Risky Behaviors Based on Cognitive Emotion Regulation with the Mediating Role of Self-Control in Adolescents - Asadi, Mansureh; Kouroshnia, Maryam; Zarnaghash, Maryam; Barzegar, Majid (Mental Health and Lifestyle Journal, 2025)
Risky behaviors during adolescence are considered one of the serious challenges in the field of mental and social health, which can lead to broad negative consequences for both the individual and society. The present study aimed to develop a model of the tendency toward risky behaviors based on cognitive emotion regulation, with the mediating role of self-control in adolescents. This study, which was descriptive-correlational in nature and based on structural equation modeling, included 312 students (158 girls and 154 boys), aged 13 to 16 years, from Jahrom city during the 2023–2024 academic year, who were selected through a multistage cluster sampling method. Participants completed the Risk-Taking Scale by Zadeh-Mohammadi et al. (2011), the Tangney Self-Control Scale (2004), and the Cognitive Emotion Regulation Questionnaire by Garnefski et al. (2006). The results of structural equation modeling showed that the proposed model had a good fit. Both self-control and adaptive cognitive emotion regulation strategies had a significant and negative direct effect on risky behaviors, while maladaptive cognitive emotion regulation strategies had a significant and positive direct effect on risky behaviors. Moreover, through the mediating role of self-control, adaptive cognitive emotion regulation strategies had a significant indirect negative effect on risky behaviors, and maladaptive strategies had a significant indirect positive effect on risky behaviors. The findings of this study demonstrated that cognitive emotion regulation plays an important role in predicting the tendency toward risky behaviors in adolescents, and this effect is partially mediated by self-control. Accordingly, it can be concluded that strengthening emotion regulation and self-control skills may serve as effective strategies in reducing risky behaviors among adolescents.